Role of Nanotechnology for Enzyme Replacement Therapy in Lysosomal Diseases. A Focus on Gaucher’s Disease - Martín-Banderas, L.; Holgado, M.A.; Durán-Lobato, M.; Infante, J.J.; æ#129;lvarez-Fuentes, J.; Fernández-Arévalo, M. (Current Medicinal Chemistry, 2016)
Lysosomal storage diseases (LSDs) comprise a group of rare inherited chronic syndromes that cause deficiency of specific native enzymes within the lysosomes. The macromolecular compounds that are usually catabolized by lysosomal enzymes are accumulated within these organelles, causing progressive damage to tissues, skeleton and organs and, in several cases, the central nervous system (CNS). The damage caused by substrate accumulation finally results in physical deterioration, functional impairment and potential death. Up to date, the most promising therapy for most LSDs is enzyme-replacement therapy (ERT), which provides patients with the corresponding active enzyme. However, these enzymes do not have enough stability in blood, the treatment must be therefore periodically administrated by i.v. infusion under medical supervision, and immunogenicity issues are frequent. In addition, affected areas within the CNS, where the blood-brain barrier (BBB) is a major obstacle, cannot be reached by the enzymes. Nanotechnology can provide useful carriers to successfully protect and preserve enzymes, and transport them through the BBB towards brain locations. Several strategies based on targeting specific receptors on the BBB have led to nanoparticles that successfully carry sensitive molecules to the brain. Then, the main LSDs are described and a thorough review of nanotechnology strategies for brain delivery studied up to date is presented.
Keywords: Gaucher’s disease